Aberrant activity in retinal degeneration impairs central visual processing and relies on Cx36-containing gap junctions. (September 2016) - Ivanova, Elena; Yee, Christopher W.; Baldoni, Robert; Sagdullaev, Botir T.
Abstract: In retinal degenerative disease (RD), the diminished light signal from dying photoreceptors has been considered the sole cause of visual impairment. Recent studies show a 10-fold increase in spontaneous activity in the RD network, challenging this paradigm. This aberrant activity forms a new barrier for the light signal, and not only exacerbates the loss of vision, but also may stand in the way of visual restoration. This activity originates in AII amacrine cells and relies on excessive activation of gap junctions. However, it remains unclear whether aberrant activity affects central visual processing and what mechanisms lead to this excessive activation of gap junctions. By combining genetic manipulation with electrophysiological recordings of light-induced activity in both living mice and isolated wholemount retina, we demonstrate that aberrant activity extends along retinotectal projections to alter activity in higher brain centers. Next, to selectively eliminate Cx36-containing gap junctions, which are the primary type expressed by AII amacrine cells, we crossed rd10 mice, a slow-degenerating model of RD, with Cx36 knockout mice. We found that retinal aberrant activity was reduced in the rd10 / Cx36 KO mice compared to rd10 controls, a direct evidence for involvement of Cx36-containing gap junctions in generating aberrant activity in RD. These data provide an essential support for future experiments to determine if selectively targeting these gap junctions could be a valid strategy for reducing aberrant activity and restoring light responses in RD. Highlights: The aberrant activity within the degenerated retina impairs visual information processing. The negative effect is more prominent due to temporal bursting structure of the aberrant activity. The aberrant activity is transferred to the retinal targets in the brain, affecting visual perception in RD. The altered gap-junction coupling of the retinal amacrine cells is essential for generating aberrant activity in RD.